2009
DOI: 10.1007/s11665-008-9298-1
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Investigations on the Loads Carried by the Tool During Friction Stir Welding

Abstract: A computational fluid dynamics (CFD) model is presented for simulating the material flow and heat transfer in the friction stir welding (FSW) of 6061-T6 aluminum alloy (AA6061). The goal is to utilize the 3-D, numerical model to analyze the viscous and inertia loads applied to the FSW tool by varying the welding parameters. To extend the FSW process modeling, in this study, the temperature-dependant material properties as well as the stick/slip condition are considered where the material at the proximity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
79
0
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(87 citation statements)
references
References 23 publications
2
79
0
6
Order By: Relevance
“…2a. Previous work by Schmidt et al [15] and Atharifar et al [12] showed experimentally that sticking conditions are closer to the real contact situation between the tool and workpiece. Cox et al [16] carried out a CFD model on FSW and assumed pure sticking conditions at the tool/workpiece contact area.…”
Section: The Mathematical Modelmentioning
confidence: 74%
See 4 more Smart Citations
“…2a. Previous work by Schmidt et al [15] and Atharifar et al [12] showed experimentally that sticking conditions are closer to the real contact situation between the tool and workpiece. Cox et al [16] carried out a CFD model on FSW and assumed pure sticking conditions at the tool/workpiece contact area.…”
Section: The Mathematical Modelmentioning
confidence: 74%
“…25 [25]. Atharifar et al [12] also reported a decrease in torque with increasing tool rotational speed and decreasing travers speed as a result of a low viscosity field resulting from an accumulation in thermal energy. From this discussion, it is expected that torque increases with increasing traverse speed at a constant tool rotational speed.…”
Section: Torquementioning
confidence: 98%
See 3 more Smart Citations